Effect of cultural conditions on lipase production Pseudomonas aeruginosa isolated from Iraqi soil (World Journal of Experimental Biosciences, 2014)
Seventy Pseudomonas isolates were obtained from different Iraqi soils samples. Thirty five of these isolates have the ability to produce lipase. These isolates were screened on Rhan medium. The highest lipase activity was found with P. aeruginosa. ps12. The effect of media composition, pH and temperature on production of lipase were determined. Maximum lipase production appeared in the medium containing (0.5%) glucose as carbon source, (0.5%) urea as nitrogen source and 1% of olive oil with pH 8 and incubated at 30 OC for 48 h with 1 ml (O.D 600= 0.8) of 24 h of bacterial culture.